Field Performance of Tissue Culture and Standard Propagated Raspberry Under Different Irrigation Regimes - Tatjana Anđelić; Jelena Tomić; Boris Rilak; Žaklina Karaklajić-Stajić; Jasminka Milivojević; Dragan Radivojević; Tatjana Vujović (Horticulturae)
Healthy plant material that is uniform and genetically pure is essential for the successful raspberries production since it guarantees quality and consistent yields. A 4-year study (2018–2021) focused on raspberry cultivars “Meeker” and “Willamette”, which were propagated by tissue culture (MpP) and root suckering (RsP) methods in three irrigation regimes (IR1-100% ETc, IR2-50% ETc, and IR3-25% ETc). “Meeker” had longer primocanes, higher productivity, sweetness, soluble solids, and sugar content in IR1. Micropropagated plants demonstrated initially longer primocanes (177.9 cm in 2018 and 203.5 cm in 2019) and slightly better productivity compared to root-suckered plants. Over time, the growth rates of plants obtained by two vegetative propagation methods became similar. The IR1 irrigation regime maximized yields per floricane and meter of trellis in 2019 and 2021 (619.8 and 501.9 g and 2.5 and 2.0 kg, respectively), providing sufficient water for raspberry plants. IR1 improved primocane height in 2018 and 2021 (181.3 and 238.3 cm), fruiting lateral length (31 cm), and number of flowers per fruiting lateral (10.7) in 2021. In all experimental years, “Meeker” showed a high sweetness index (8.53, 11.28, and 9.36) due to high sugar and low acid content, but it was sensitive to water deficit. “Willamette” maintained high total anthocyanins and stable sugar content, which emphasizes its adaptability to different conditions. Both cultivars showed high antioxidant activity with variability across study years. Antioxidant activity peaked in 2019 under all irrigation regimes and remained stable in 2021. The cultivar “Meeker” excelled in vegetative growth, productivity, and fruit taste, making it suitable for obtaining high yields in a 100% ETc irrigation level. In contrast, “Willamette” is better suited for obtaining high-quality fruit under water-limited conditions.